2021
DOI: 10.3389/fviro.2021.724016
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Saliva Modulates Japanese Encephalitis Virus Infection in Domestic Pigs

Abstract: Japanese encephalitis virus (JEV) is a mosquito-borne flavivirus that is the leading cause of pediatric viral encephalitis in Asia. Japanese encephalitis virus is transmitted by Culex species mosquitoes that also vector several zoonotic flaviviruses. Despite the knowledge that mosquito saliva contains molecules that may alter flavivirus pathogenesis, whether or not the deposition of viruses by infected mosquitoes has an impact on the kinetics and severity of JEV infection has not been thoroughly examined, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…However, natural infection and disease in young piglets are not commonly reported from the endemic areas, possibly due to the presence of maternal antibodies, which can last up to six months of age [ 46 , 47 ]. While non-specific clinical signs such as fever, anorexia, and depression are observed early with JEV infection, neurologic signs such as hind limb tremors or ataxia can sometimes develop after five days post-infection [ 48 , 49 , 50 , 51 , 52 ]. Some infected pigs can progress into developing a wasting-like syndrome [ 52 , 53 ].…”
Section: Je Disease In Swinementioning
confidence: 99%
See 4 more Smart Citations
“…However, natural infection and disease in young piglets are not commonly reported from the endemic areas, possibly due to the presence of maternal antibodies, which can last up to six months of age [ 46 , 47 ]. While non-specific clinical signs such as fever, anorexia, and depression are observed early with JEV infection, neurologic signs such as hind limb tremors or ataxia can sometimes develop after five days post-infection [ 48 , 49 , 50 , 51 , 52 ]. Some infected pigs can progress into developing a wasting-like syndrome [ 52 , 53 ].…”
Section: Je Disease In Swinementioning
confidence: 99%
“…To date, laboratory studies have demonstrated that domestic pigs from various geographic regions are all susceptible to JEV and can be infected with the representative strains of endemic GI-b and GIII using different routes of infection, including intravenous, subcutaneous, intradermal, and intranasal challenge [ 19 , 51 , 52 , 53 , 66 ]. Similar pathologic outcomes and immune responses were observed in these infected pigs regardless of the challenge modality [ 19 , 66 ].…”
Section: Jev Viremia In Infected Pigs: An Important Pathological Outc...mentioning
confidence: 99%
See 3 more Smart Citations